Impact of ethical leadership in HRM on employee’s turnover intention post Covid-19 - Singh, Rashmi; Tarkar, Preeti (Brazilian Journal of Operations & Production Management, 2023)
Goal: The paper aims to identify ethical leadership’s efficacy in HRM and differentiate it from negative HRM leadership. Pandemic and post-pandemic challenges are evident, which can destabilize an organization, so we need to develop a business-ethics perspective on leadership for HRM. Method: For the study, the data of 120 manufacturing companies’ employees from Uttar Pradesh has been collected. The analysis of data has been done with the help of simple linear regression and T-test through SPSS. Results: The research on the concerned issue and critically reflects on negative leadership issues that arise post-Covid-19. The analysis results have concluded that there is a positive impact of ethical leadership on employee turnover intention post-covid-19 in Uttar Pradesh, and there is no significant difference in the perception of male and female respondents towards turnover intentions post-covid-19. Limitations: The study is a small-scale study consisting of 120 employees from manufacturing companies; for future research, the data can be collected for conducting a large-scale study. Pratical implication: The study will be helpful for organizations to know about the impact of covid-19 on HRM and will lead to creating an understanding of the need of developing ethical leadership in HRM to deal with the turnover intentions of employees at the time of crisis. Originility: There has been various previous studies which talk about the employees turnover intentions during covid-19, while there is no previous literature available which states about the turnover intentions of employees post covid-19 in Uttar Pradesh, India. Moreover, the study is discussing the situation from an ethical perspective which is an addition to the existing literature.